Al-Sayyid Abu Al-Hasan ’Ali Al-Nadwi: Tema-tema Besar Pemikirannya - Fadzil, Siddiq (Jurnal Usuluddin, 2000)
The article tries to analyze al-Nadwi’s thought especially his idea of Tajdid. It covers his views on a number of major issues such as western civilization, the concept of Prophetic, Islamic education and literature and Islamic resurgence.